Effect of Recycling Protocol on Mechanical Strength of Used Mini-Implants - Sérgio Estelita; Guilherme Janson; Kelly Chiqueto; Eduardo Silveira Ferreira (Hindawi Limited, 2014)
Purpose. This study evaluated the influence of recycling process on the torsional strength of mini-implants. Materials and Methods. Two hundred mini-implants were divided into 4 groups with 50 screws equally distributed in five diameters (1.3 to 1.7 mm): control group (CG): unused mini-implants, G1: mini-implants inserted in pig iliac bone and removed, G2: same protocol of group 1 followed by sonication for cleaning and autoclave sterilization, and G3: same insertion protocol of group 1 followed by sonication for cleaning before and after sandblasting (Al2O3-90 µ) and autoclave sterilization. G2 and G3 mini-implants were weighed after recycling process to evaluate weight loss (W). All the screws were broken to determine the fracture torque (FT). The influence of recycling process on FT and W was evaluated by ANOVA, Mann-Whitney, and multiple linear regression analysis. Results. FT was not influenced by recycling protocols even when sandblasting was added. Sandblasting caused weight loss due to abrasive mechanical stripping of screw surface. Screw diameter was the only variable that affected FT. Conclusions. Torsional strengths of screws that underwent the recycling protocols were not changed. Thus, screw diameter choice can be a more critical step to avoid screw fracture than recycling decision.